2020
DOI: 10.1152/jn.00220.2020
|View full text |Cite
|
Sign up to set email alerts
|

Humans sacrifice decision-making for action execution when a demanding control of movement is required

Abstract: A growing body of evidence suggests that decision-making and action execution are governed by partly overlapping operating principles. Especially, previous work proposed that a shared decision urgency/movement vigor signal, possibly computed in the basal ganglia, coordinates both deliberation and movement durations in a way that maximizes the reward rate. Recent data support one aspect of this hypothesis, indicating that the urgency level at which a decision is made influences the vigor of the movemen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
70
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(77 citation statements)
references
References 57 publications
4
70
2
Order By: Relevance
“…Speiser et al ( 2017 ) found that, under certain conditions, the SAT mechanism in decisional processes can speed up motor-specific preparation (reflected in a faster build-up of EMG-activity), and produce faster movements (but increased overt errors). Indeed, until recently, it was thought that decision urgency and movement vigour may constitute a unique ‘invigoration’ signal, influencing latencies in both decisional and motor processes (see Reynaud et al, 2020 ). In this account, the self-advantage in RT could drive the self-advantage in MT through a shared invigoration signal.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Speiser et al ( 2017 ) found that, under certain conditions, the SAT mechanism in decisional processes can speed up motor-specific preparation (reflected in a faster build-up of EMG-activity), and produce faster movements (but increased overt errors). Indeed, until recently, it was thought that decision urgency and movement vigour may constitute a unique ‘invigoration’ signal, influencing latencies in both decisional and motor processes (see Reynaud et al, 2020 ). In this account, the self-advantage in RT could drive the self-advantage in MT through a shared invigoration signal.…”
Section: Discussionmentioning
confidence: 99%
“…In this account, the self-advantage in RT could drive the self-advantage in MT through a shared invigoration signal. However, recent work has shown that decisional urgency and movement vigour are actually independent (albeit interacting) signals (Reynaud et al, 2020 ). In line with this, a recent study by Barton et al ( 2020 ) found that self-mug ownership shortened both RT and MT in approach movements and only RT in (participant-body-directed) avoidance movements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations